2008
DOI: 10.1039/b717811e
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium based ionic liquids in soils: effects of the side chain length on wheat (Triticum aestivum) and cress (Lepidium sativum) as affected by different clays and organic matter

Abstract: This study provides data on the behaviour and toxicity of selected imidazolium based ionic liquids in the terrestrial environment with the aim to contribute to a prospective hazard assessment. Using the plant growth inhibition assay with wheat (Triticum aestivum) and cress (Lepidium sativum) we investigated the influence of two different clay minerals (kaolinite and smectite) in varying concentrations and clay mineral mixtures as well as the influence of organic matter in varying concentrations on the toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 41 publications
6
65
0
2
Order By: Relevance
“…The quoted literature shows that a likely toxic influence of a ionic liquid is determined by a number of factors, of which the primary role is played the cation type and the length of the substituent in the cation (as a rule, the longer alkyl chain, the higher toxicity). The anion type is not without significance, either; but the concentration of the substance used and the habitat conditions, including the presence of other xenobiotics, and the species features of the organism tested are also all-important [1,4,8,9,15,17,18,21,36,37]. The studies of the potential ecotoxicity of ionic liquids has not only a learning and ecological aspect, which eliminates the risk of failure in the process of issuing permits for industrial use and trade in these substances, but are also important for economic reasons, as they prevent any financial expenditures on the rectification of possible damage in the natural environment [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quoted literature shows that a likely toxic influence of a ionic liquid is determined by a number of factors, of which the primary role is played the cation type and the length of the substituent in the cation (as a rule, the longer alkyl chain, the higher toxicity). The anion type is not without significance, either; but the concentration of the substance used and the habitat conditions, including the presence of other xenobiotics, and the species features of the organism tested are also all-important [1,4,8,9,15,17,18,21,36,37]. The studies of the potential ecotoxicity of ionic liquids has not only a learning and ecological aspect, which eliminates the risk of failure in the process of issuing permits for industrial use and trade in these substances, but are also important for economic reasons, as they prevent any financial expenditures on the rectification of possible damage in the natural environment [29].…”
Section: Introductionmentioning
confidence: 99%
“…With reference to this problem, along with scientific reports on the synthesis, physical and chemical properties and the potential for practical utilization of ionic liquids, a large number of studies have come up, which are concerned with the examination of the potential toxicity of these substances. Studies described in available literature reveal varied influences of ionic liquids on microorganisms [1,2,[17][18][19][20][21][22], plankton [21,[23][24][25][26], invertebrates [27][28][29], vertebrates [27,30], algae [2,21,23,29,[31][32][33], fungi [19,34,35] or higher land plants [8,21,31,[36][37][38][39]. The quoted literature shows that a likely toxic influence of a ionic liquid is determined by a number of factors, of which the primary role is played the cation type and the length of the substituent in the cation (as a rule, the longer alkyl chain, the higher toxicity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been reported to possess antibacterial activity, cytoxicity and toxicity towards multicellular organisms, 162 and ecotoxicity in the case of aquatic organisms and terrestrial plants. 163,164 3.4. Novel application of fluorous solvents in product isolation following biocatalysis An interesting application of solvents for biocatalysis was developed in 2002 by Theil et al [165][166][167] Initially lipase-mediated kinetic resolution of a range of alcohols with fluorous esters was performed and repeated washing with the fluorous solvent removed the transformed ester in high enantiopurity with the untransformed alcohol remaining in the organic phase also in excellent enantiopurity.…”
Section: Anionmentioning
confidence: 99%
“…Although ILs will not cause air pollution because of their negligible vapor pressures, some of them still present a non-negligible solubility in water, thus leading to aquatic environmental risks [9]. Several studies have reported the biological effects of single ILs on the basis of different toxicological test systems such as enzymes (e.g., acetylcholinesterase), bacteria (e.g., Vibrio fischeri), algae (e.g., Selenastrum capricornutum), mammalian cells (e.g., MCF-7 cell), plants (e.g., wheat and cress), invertebrates (e.g., zebra mussel), and vertebrates (e.g., Danio rerio) [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%